UNDIVIDED INHERITANCE AS A UNIT IN LIEU OF THE BENEFICIARIES: A TAX FAIRNESS PERSPECTIVE - Dino Sulistomo (Scientia Integritas Utama, 2022)
The self-assessment system in Indonesia has not maximized the tax potential for inheritances that have not been divided as a unit replacing those entitled as income tax subjects. It is necessary to build tax provisions that apply to undivided inheritance in Indonesia to produce a fair legal concept for the potential of inheritance that has not been divided as a unit to replace the rightful in the future in Indonesia. The study yielded two conclusions based on normative juridical methods with a qualitative approach. First, the tax provisions that apply to undivided inheritance in Indonesia as stipulated in Article 2 paragraph (1) a number 2) and Article and explanation 2A paragraph (5) of the Income Tax Law, and Article 32 paragraph (1) letter (e) of the KUP Law still ignore tax fairness. Second, it is necessary to reformulate the law on undivided inheritance. It attaches propriety to act or do and decency not to act or not act to the taxpayer and the tax apparatus. It is recommended that there are rules and or procedures for cooperation in the form of data exchange between DGT and several related institutions, such as local government and heritage hall.